Empowering local communities through digital marketing automation: A case study of eco-friendly dragon fruit kombucha - Aldy Iqbal Syafruddin; Imelda Putri Febriana; Annurul Zahwa; Lulus Putri Aninda (Social Agriculture, Food System, and Environmental Sustainability, 2026)
Background: This study examines the application of automation technology in the production of environmentally friendly dragon fruit-based kombucha in Kediri using the n8n platform. Kombucha is a fermented beverage that has attracted growing consumer interest due to its potential health benefits, while dragon fruit serves as a natural ingredient with added nutritional value. Methods: The study employs a research and development (R&D) approach aimed at improving production efficiency and maintaining product quality. Automation is applied to several stages of the production process, including raw material management, fermentation time regulation, as well as distribution and marketing activities. The development process is based on the Borg and Gall model, which emphasizes systematic testing and evaluation at each stage of product development. This approach allows for continuous refinement to ensure the feasibility and effectiveness of the production system. Findings: The results of the study show that the integration of the n8n platform has successfully automated key workflows, from monitoring raw materials to managing fermentation times and marketing distribution. This implementation has significantly improved operational efficiency by reducing dependence on manual processes and minimizing the risk of human error. From a product perspective, consumer trials showed a high level of acceptance; dragon fruit kombucha produced by this system was rated superior in terms of flavor balance, fresh aroma, and attractive natural color. Conclusion: This study concludes that the use of low-code automation technology such as n8n is an effective solution for optimizing the production and marketing of environmentally friendly kombucha at the local level. Novelty/Originality of this article: The novelty of this research lies in the use of the n8n platform—which is commonly used for pure IT workflows—in the context of MSME-scale fermented beverage production.